Sustainability of Agroecosystems - Bosco de Oliveira, Alexandre (IntechOpen, 2018)
The present book is composed of modern theoretical and applied studies that highlight the core principles and evidence of sustainable agriculture. This work is systematically divided into two sections, which summarize crucial insights into this theme, such as agroecological concepts, case studies, soil health, and agroforestry systems. The chapters included in this book have been written by researchers whose expertise allows the relatively complex sustainable agroecosystem-related topics to be easily understood by any reader. Therefore, the target audience comprises not only scholars and specialists in the field but also common people and enthusiasts about this theme. Such chapter's collection is certainly a valuable resource about agricultural sustainable principles and a pleasure reading for those who are willing to dive more deeply into the study of "sustainability of agroecosystems."